Mutations in E.coli 16s rRNA that enhance and decrease the activity of a suppressor tRNA. - Prescott, C D (1992)
The in vivo expression of mutations constructed within helix 34 of 16S rRNA has been examined together with a nonsense tRNA suppressor for their action at stop codons. The data revealed two novel results: in contrast to previous findings, some of the rRNA mutations affected suppression at UAA and UAG nonsense codons. Secondly, both an increase and a decrease in the efficiency of the suppressor tRNA were induced by the mutations. This is the first report that rRNA mutations decreased the efficiency of a suppressor tRNA. The data are interpreted as there being competition between the two release factors (RF-1 and RF-2) for an overlapping domain and that helix 34 influences this interaction.